The application of load identification model on the weld line fatigue life assessment for a wheel loader boom. (October 2019) - Yuan, Zhengwen; Ma, Hongfeng; Lu, Yongneng; Zhu, Shumin; Hong, Tao
Abstract: The external loads on the wheel loader are essential for structural fatigue life assessment. However, the external loads are hard to be acquired, because the contact force between the soil and the working device is very complex. Most researchers obtain the external loads using dynamic simulation and theoretical analysis, whereas there is a big gap between the simulation and the reality. In order to obtain the precise external loads of the wheel loader, a load identification model verified by test is proposed in this paper. The mathematical relationship between the external loads and loads at the hinged points of the wheel loader is deduced from mechanical balance equation, and the load identification theoretical model is established. Based on the load identification model, a load test system is designed and the test is carried out. Based on the time history of strain measurement near the fatigue weak points and the Miner's damage theory, the relative damage is calculated to ensure that the relative damage ratio of the weak life point between the measured and simulated value is less than 0.8. Finally, the external loads obtained by the load identification model are taken as the input condition, and the life of the boom weld structure is evaluated by the mesh-insensitive structural stress method (MSS method). The results show that the calculated weak point life can truly reflect the actual weld failure position and the error ratio between predicted and actual lives is within one magnitude, which can meet the needs of engineering applications. Highlights: The relationship between the external loads and loads at the hinged points is deduced. A load test system and customized sensors are designed. The relative damage ratio is calculated to evaluate the gap between the simulation and test results. The load data is applied to weld line fatigue life assessment.